Effect of In Vitro Exposure of Corticosteroid Drugs, Conventionally Used in AMD Treatment, on Mesenchymal Stem Cells. (23rd May 2012) - Nuzzi, Raffaele; Gunetti, Monica; Rustichelli, Deborah; Roagna, Barbara; Fronticelli Bardelli, Francesca; Fagioli, Franca; Ferrero, Ivana
Abstract : Age-related macular degeneration (AMD) is a leading cause of legal blindness in individuals over 60 years of age, characterized by the dysfunction of retinal pigmented epithelium cells, specifically in the macular area. Despite several treatment options, AMD therapy remains difficult, especially for exudative AMD. Multipotent mesenchymal stem cells (MSCs), with great plasticity and immunomodulant properties, are a promising cell source for cellular therapy and tissue engineering. We evaluated the effects of steroid drugs, often used to treat AMD, in association with MSCs, in view of a possible application together to treat AMD. Morphology, viability, growth kinetics, and immunophenotype were evaluated on healthy donors' MSCs, treated with triamcinolone acetonide, alcohol-free triamcinolone acetonide, micronized intravitreal triamcinolone and dexamethasone at different concentrations, and in a human retinal pigment epithelial cell line supernatant (ARPE-19). The morphological analysis of MSCs in their standard medium showed a negative correlation with drug concentrations, due to the numerous crystals. Dexamethasone was the least toxic corticosteroid used in this study. ARPE-19 seemed to help cells preserve the typical MSC morphology. In conclusion, this in vitro study demonstrated that high doses of corticosteroid drugs have a negative effect on MSCs, reduced in the presence of a conditioned media.